2013
DOI: 10.1155/2013/539636
|View full text |Cite
|
Sign up to set email alerts
|

A Green Approach to Synthesize Silver Nanoparticles in Starch-co-Poly(acrylamide) Hydrogels by Tridax procumbens Leaf Extract and Their Antibacterial Activity

Abstract: A series of starch-co-poly(acrylamide) (starch-co-PAAm) hydrogels were synthesized by employing free radical redox polymerization. A novel green approach, Tridax procumbens (TD) leaf extract, was used for reduction of silver ions (Ag+) into silver nanoparticles in the starch-co-PAAm hydrogel network. The formation of silver nanoparticles was confirmed by UV-visible spectroscopy (UV-Vis), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The antibacterial activity of SNPs‐IPN beads in terms of zone of inhibition developed against both types of bacteria (gram positive and negative bacteria) can be compared with reported literature and it is found that the diameter of the zone of inhibition against both types of bacteria using the SNPs‐IPN beads was more than some of SNPs comprising polymer composites . This indicates that the prepared SNPs‐IPN beads are promising disinfecting agent for water purification.…”
Section: Resultsmentioning
confidence: 80%
“…The antibacterial activity of SNPs‐IPN beads in terms of zone of inhibition developed against both types of bacteria (gram positive and negative bacteria) can be compared with reported literature and it is found that the diameter of the zone of inhibition against both types of bacteria using the SNPs‐IPN beads was more than some of SNPs comprising polymer composites . This indicates that the prepared SNPs‐IPN beads are promising disinfecting agent for water purification.…”
Section: Resultsmentioning
confidence: 80%
“…The other reason may be that the formed nanoparticles have different sizes with different surface charges in the gel networks causing absolute expansion of the networks (Siraj et al, 2013). Increase of crosslinker concentration in the hydrogel synthesis leads to decreased swelling capacities of hydrogels ( Fig 6C).…”
Section: Swelling Studiesmentioning
confidence: 99%
“…Globally, lignin is regarded as an unrefined material with a high recovery potential, easy to get from the renewable sources, with low costs and an insignificant pollution degree (Totolin et al, 2010;Sekhar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experimental methods for the removal of heavy elements are used with a combination for different techniques such as membrane and electrolysis [3][4][5]. The extraction of heavy metal ions as pollutants from water pollution, using electrochemical methods, is important [6][7][8][9]. Several metal ions in solutions can be recovered by reduction at the cathode.…”
Section: Introductionmentioning
confidence: 99%